IMPLEMENTASI PEMAKAIAN GELANG IDENTITAS TERHADAP KESELAMATAN PASIEN DI RUMAH SAKIT UMUM MITRA MEDIKA TANJUNG MULIA - Dilla Fitria; Andini Mentari Tarigan; Ribka Panjaitan (ZAHRA: JOURNAL OF HEALTH AND MEDICAL RESEARCH, 2023)
The use of an identity bracelet is one of the implementations of correct identification which is 1 of the 6 Patient Safety Goals regulated in PERMENKES No. 1691 of 2011. Wristband installation is done by the emergency room nurse and is verified every time the nurse will take action. Identity bracelets are distinguished by color criteria, namely pink, blue, white, red, yellow, and purple. The purpose of installing a bracelet at the time of service is to ensure the accuracy of the patient who will receive the service or action required by the patient. This study aims to determine the implementation of the use of identity bracelets on patient safety at Mitra Medika General Hospital Tanjung Mulia Medan in. This research used descriptive qualitative, the informants used in this study was 7 people. The results obtained by the hospital have established a policy regarding Standard Operating Procedures related to the implementation of accurate patient identification at Hospital and adapted to the latest version of the hospital's accreditation standard. Assisted by the well-organized flow of patient safety incident reporting in hospitals to make it easier to follow up on problems that arise. The conclusion shows that the target in implementing the use of a good identity bracelet is that there must be good collaboration and communication among colleagues or teams.